O rio e o caminho natural: propostas de canais do São Francisco, aspectos físicos fluviais e dinâmicas políticas no Brasil Império (1846-1886) - Gabriel Pereira de Oliveira (2015)
Subject of controversial debate in recent years, the transposition of the São Francisco River is not absolutely a new project. In the mid-nineteenth century, the so-called idea of channeling canal waters at this river was an object of intense discussions. In dialogue especially with the environmental historys approach and the political studies about the Brazil Empire, this research investigates the propositions of the São Francisco canal between 1846 and 1886. During this period, defined respectively by parliamentary and technical requests, the canalization was related peculiarly to issues such as transport and drought. However these issues were far to be solved consensually. The canal proposals were in the middle of hard disputes among themselves, railways and weirs. By analyzing sources like maps, technical studies or parliamentary speeches, this study will assay the canal proposals amid conflicts about the control of São Francisco circulations and the way to overcome drought problems. In this process, members of several provinces tried to legitimize their respective projects anyway into a web of nature and power. Although the plan - presented as a symbol of modernity - have not been implemented, the knowledge about their discussions and non-achievement allows the thought about the links between social groups and nature, as well as disputes and political arrangements in nineteenth-century Brazil.